Pengembangan Pariwisata Alam Berbasis Community Based Tourism di Kawasan Wisata Mengger Omah Kinjeng - Atmojo, Muhammad Eko; Darumurti, Awang; Fridayani, Helen Dian; Hanif, Nita Aribah (PANDAWA : Jurnal Pengabdian kepada Masyarakat, 2024)
Hargorejo Village is a village that has a lot of potential, ranging from potential, agriculture, tourism to the potential of MSMEs. With the existence of very supportive geographical conditions, it is important for village governments to realize and implement tourism villages. So that the improvement of the community economy does not only come from one source but can come from various sectors. So far, Hargorejo village is famous for MSMEs and tourism, but the tourism sector has not been managed seriously so that there is still a lot of potential that has not been maximized to be promoted. The methods offered through the community service program include: (1) conducting tourism branding training and socializing the importance of branding for the world of tourism, 2) revitalize tourism ranging from human resources to supporting resources such as branding and social media, (3) install signposts and directions for tourist attractions. Based on the results of the service that has been carried out, tourism branding is formed in an integrated manner and managed by the Tourism Village. In addition, managers of tourist attractions can also understand the importance of branding and the use of information technology for tourism promotion